FEATURES OF THE TRANSLATION OF CULINARY NAMES BASED ON THE MATERIAL OF CULINARY RECIPES (Proceedings of International Educators Conference, 2023)
Culinary names are the names of dishes and confectionery products. At the moment, there is still no special section of onomastics that would study the features of this lexico-semantic category. However, culinary names are widely used in special, fiction literature, periodicals and everyday speech. Culinary names combine the capacity of meaning and brevity: behind each name of the dish there is a recipe. Culinary names can perform symbolizing, thematizing or evaluative functions. Culinary names reflect the realities of traditional life. They are connected with the history of the formation of national cuisine and belong to long-term background knowledge.